Risk and protective factors for meningococcal disease in adolescents: matched cohort study. Issue 7539 (10th February 2006) - Tully, Joanna; Viner, Russell M; Coen, Pietro G; Stuart, James M; Zambon, Maria; Peckham, Catherine; Booth, Clare; Klein, Nigel; Kaczmarski, Ed; Booy, Robert
Abstract: Objective To examine biological and social risk factors for meningococcal disease in adolescents. Design Prospective, population based, matched cohort study with controls matched for age and sex in 1:1 matching. Controls were sought from the general practitioner. Setting Six contiguous regions of England, which represent some 65% of the country's population. Participants 15-19 year olds with meningococcal disease recruited at hospital admission in six regions (representing 65% of the population of England) from January 1999 to June 2000, and their matched controls. Methods Blood samples and pernasal and throat swabs were taken from case patients at admission to hospital and from cases and matched controls at interview. Data on potential risk factors were gathered by confidential interview. Data were analysed by using univariate and multivariate conditional logistic regression. Results 144 case control pairs were recruited (74 male (51%); median age 17.6). 114 cases (79%) were confirmed microbiologically. Significant independent risk factors for meningococcal disease were history of preceding illness (matched odds ratio 2.9, 95% confidence interval 1.4 to 5.9), intimate kissing with multiple partners (3.7, 1.7 to 8.1), being a university student (3.4, 1.2 to 10) and preterm birth (3.7, 1.0 to 13.5). Religious observance (0.09, 0.02 to 0.6) and meningococcal vaccination (0.12, 0.04 to 0.4) were associated with protection. Conclusions Activities and events increasing risk for meningococcal disease in adolescence are different from in childhood. Students are at higher risk. Altering personal behaviours could moderate the risk. However, the development of further effective meningococcal vaccines remains a key public health priority.